The exploration of the role of Financial Constraints in Mediating the link between ESG and Financial Performance: The Case of the Oil & Gas industry - Ning, Zirui (2022)
The United Nations Principles for Responsible Investment formally proposed the Environmental Social and Governance (ESG) principle in 2004. Since then, a large number of research on the link between firms' ESG performance and their financial performance have been conducted. However, the channel behind in terms of how ESG impacts financial performance was rarely studied. Hence, the main purpose of this study is to research the potential mediating role of financial constraints on the relationship between ESG and corporate financial performance. Taking companies in the Oil & Gas industry as the sample, the study used the five-step mediating effect testing method to analyze 10-year panel data, with Refinitiv's ESG rating serving as a proxy variable for ESG performance. The findings of this research indicate that better ESG ratings would help to improve the company's financial performance, with reduced financial constraints playing a partial mediating effect. Additionally, this study went into further detail to describe which features of the ESG created such an outcome. With the finding that the Environmental aspect hinders the total effect of ESG, and the Social pillar contributes to it, this study also validates the presence of prior research that shows no substantial association or suggests a contrary viewpoint.